Five Great Families and Telepathy: Folk Religion and Buddhism in Neo-Dongbei Fiction by Zheng Zhi - Wang, Aiqing (AL-ADYAN, 2021)
The 2010s has witnessed the visibility of literature based on China’s Northeast (Dongbei), exemplified by literary works composed by Zheng Zhi, Ban Yu and Shuang Xuetao, viz. the ‘three masters of Dongbei Renaissance’. In a 2020 novella anthology, Zheng Zhi expatiates upon a veritable cornucopia of representations of folk religion (aka popular religion) and established religions via depictions concerning shamanism, Buddhism and Christianity. In a narrative entitled Xian Zheng ‘Divine Illness’, Zheng Zhi manifests animal worship as a form of folk religion, by means of painting a vivid portrait of shamanic practices pertaining to ‘five major deity families’ that denotes fox, weasel, hedgehog, snake and rat spirits. In a narrative entitled Taxintong ‘Telepathy’, Zheng Zhi depicts Buddhist practices, the preponderant motivations for which are analogous to those for folk religion in contemporary Dongbei, namely, physical wellbeing and psychological solace.